Labour supply and commuting - Eva Gutiérrez-i-Puigarnau; Jos van Ommeren (Institute for the Study of Labor (IZA), 2010)
A new paradigm for transport economists has been established: revenues of a welfare-maximising road tax should be employed to reduce the level of a distortionary income tax. An essential modelling assumption to reach this conclusion is that the number of workdays is optimally chosen, whereas daily workhours are fixed, implying that given a road tax, workers may only reduce their commuting costs by reducing total labour supply. However, a labour supply model which also allows for optimally chosen daily hours implies that commuting costs increase daily hours, whereas the effect on total labour supply is ambiguous. This paper addresses this issue empirically by analysing the relationship between labour supply patterns and commuting distance using the socio-economic panel data for Germany between 1997 and 2007. Endogeneity of commuting distance is accounted for by using employer-induced changes in commuting distance. In line with the theoretical model developed, we find that commuting distance has a positive effect on daily hours. Our analysis does not find a negative effect of commuting distance on total labour supply, suggesting that a reduction in the income tax, as advocated in the literature, may not be necessary.
Keywords: J22; R41; 330; Commuting cost; congestion tax; labour supply; Arbeitsangebot; Optimale Besteuerung; Straßenbenutzungsgebühr; Berufsverkehr; Bottleneck; Soziale Kosten; Theorie; Schätzung; Deutschland